2D sp2 Carbon‐Conjugated Covalent Organic Framework with Pyrene‐Tethered TEMPO Intercalation for Photocatalytic Aerobic Oxidation of Sulfides into Sulfoxides. Issue 1 (19th November 2021) - Shi, Ji-Long; Feng, Keyu; Hao, Huimin; Ku, Calvin; Sit, Patrick H.-L.; Teoh, Wey Yang; Lang, Xianjun
Abstract : The 2D covalent organic frameworks (COFs) offer many 2D planes which are suitable for π–π stacking interactions with other conjugated molecules. To improve the photocatalytic performance of COFs, the synthesis of a pyrene‐tethered 2, 2, 6, 6‐tetramethylpiperidinyl‐N‐oxyl (TEMPO) derivative cocatalyst is hereby described. The pyrene end of the cocatalyst is intercalated in between the layers of the 2D sp 2 carbon‐conjugated porphyrin covalent organic framework (Por‐sp 2 c‐COF) via π–π stacking interactions evidenced by theoretical and experimental studies. The immobilization of pyrene‐tethered TEMPO significantly enhances both the efficiency of photoinduced hole transfer and the stability of Por‐sp 2 c‐COF for the selective aerobic oxidation of a series of sulfides to sulfoxides under the irradiation of 623 nm red LEDs. This work highlights the merit of π–π stacking as a facile and efficient approach of immobilizing hole transfer cocatalysts without disrupting the physiochemical properties of the 2D COF photocatalyst. Abstract : π–π stacking intercalation of pyrene‐tethered 2, 2, 6, 6‐tetramethylpiperidinyl‐N‐oxyl (TEMPO) cocatalyst into a 2D covalent organic framework (COF) induces cooperative photocatalysis for red light‐driven selective aerobic oxidation of sulfides.